(3ZPGA GdCQhGM HGdeMGOKI hGdeRGMs - (3eQYj Hf jhSa Hf CHj HcQ Hf CMeO GdcQej GdebOSj GdMfHdi,J (B1033 (3g` s
(3ChdgG (B:s
(3abO CMHHJ Cf CVY HYV dWGFa hLed hXQGFa aj PcQ GdeRM, hHjGf GdeMehO efg hGdePehe s
(3BNQgG (B:s
(3CeG CHj adGf addSad hGdCQGPd haj gPG GdbOQ caGjI Je GdcJGH HMeO Gddg s
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B203 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B12 - (3U (B218s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B5 - (3U (B62 s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdeUQjI (B((3COH JjehQ (B666) s
Keywords: (3GdCOHs